Pelatihan Pembuatan Balsam Stik Dari Bahan Herbal Dan Perintisan Sebagai Home Industri - dwi - Ningsih; Sri Rejeki Handayani; Ismi - Rahmawati; Dewi - Ekowati; Desi - Purwaningsih (Adi Widya : Jurnal Pengabdian Masyarakat, 2019)
Balm, a pharmaceutical product that is no stranger to the community, therefore, this product is one of the most potential commodities developed into a home industry that can improve the economy of the community. relatively simple balm formulation and easy in material, is very possible to be applied in the community. This article is a form of publication of community service that has been carried out on Tuesday, February 6, 2018,at RW XXII Bibis Luhur Kel. Nusukan Kec. Banjarsari Surakarta Central Java. This community service is entitled "training of sticks from herbal and pioneering industry as a home industry" which aims to provide understanding and skill through counseling, training, and application of herbal balsam in the form of sticks, and utilization in health by empowering natural resources optimally, produce new products, besides can be made for self-use, sticks balm is a product that is very much needed by the community, so it is possible to develop its production in the scale of home industry to improve the economy of the community.